URGENSI ILMU TASAWUF PADA KOMUNITAS SANTRI PP. ASSUNNIYYAH KENCONG JEMBER - Zaeni, Akhmad (UAS PRESS, 2018)
Suϐism including science activities that are important to produce a self-perfection in order to be biased towards God. A santri must be an image of the example of his surroundings. The formulations in this study are (1) how are the systems and methods of Suϐism teachings taught at the as-Sunniyyah Kencong Jember Islamic Boarding School? (2) how is the implementation of Suϐism practices among santri at the as-Sunniyyah Kencong Jember Islamic Boarding School? This study uses a ϐield research model. The main sources are observations, informants, literature data and supporting documentation. For data analysis using several methods: description method and interpretation method. The purpose of this study is (1) to describe the systems and methods of Suϐism teachings that are taught at the Assunniyyah Kencong Jember Islamic Boarding School. (2) to describe the implementation of Suϐism practices among santri at the Assunniyyah Kencong Jember Islamic Boarding School.